Total intravenous anesthesia will supercede inhalational anesthesia in pediatric anesthetic practice. Issue 1 (14th October 2014) - Lauder, Gillian R.; Morton, Neil
Summary Inhalational anesthesia has dominated the practice of pediatric anesthesia. However, as the introduction of agents such as propofol, short‐acting opioids, midazolam, and dexmedetomidine a monumental change has occurred. With increasing use, the overwhelming advantages of total intravenous anesthesia (TIVA) have emerged and driven change in practice. These advantages, outlined in this review, will justify why TIVA will supercede inhalational anesthesia in future pediatric anesthetic practice.